Исследование метрологических характеристик системы измерения малых изменений температуры - Samynina, M. G.; Shigimaga, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
Metrological parameters of the non-standard contact device were investigated to characterize its performance in temperature change measurements in the specified temperature range. Several series thermistors with a negative temperature coefficient of resistance connected into a linearization circuit were used as the sensing element of the semiconductor device. Increasing the number of thermistors leads to improved circuitry resolving power and reduced dispersion of this parameter. However, there is the question of optimal ratio of the number of thermistors and implemented temperature resolution, due to the nonlinear resolution dependence of the number of series-connected thermoelements. An example of the scheme of four similar thermistors as the primary sensor and of a standard measuring instrument, which is working in ohmmeter mode, shows the ability to measure temperature changes at the level of hundredth of a Celsius degree. In this case, a quantization error, which is determined by a resolution of the measuring system, and the ohmmeter accuracy make the main contribution to the overall accuracy of measuring small temperature changes.